Growth Promotion and Increased ATP-Binding Cassette Transporters Expression by Liraglutide in Triple Negative Breast Cancer Cell Line MDA-MB-231 - Shadboorestan, Amir; Tarighi, Parastoo; Koosha, Mahsa; Faghihi, Homa; Ghahremani, Mohammad Hossein; Montazeri, Hamed (Drug Research, 2021)
Background Glucagon-like petide-1 (GLP-1) agonists such as liraglutide are widely employed in type 2 diabetes due to their glucose reducing properties and small risk of hypoglycemia. Recently, it has been shown that GLP-1agonists can inhibit breast cancer cells growth. Nonetheless, concerns are remained about liraglutide tumor promoting effects as stated by population studies.Material and Methods We evaluated the effects liraglutide on proliferation of MDA-MB-231 cells by MTT assay and then ATP-binding cassette (ABC) transporters expressions assessed by Real time PCR. Statistical comparisons were made using one-way analysis of variance followed by a post hoc Dunnett test.Results Here, we report that liraglutide can stimulate the growth of highly invasive triple negative cell line MDA-MB-231; which can be attributed to AMPK-dependent epithelial-mesenchymal transition (EMT) happening in MDA-MB-231 context. Toxicity effects were only observed with concentrations far above the serum liraglutide concentration. ATP-binding cassette (ABC) transporters expressions were upregulated, indicating the possible drug resistance and increased EMT.Conclusion In conclusion, these results suggest that liraglutide should be used with caution in patients who are suffering or have the personal history of triple negative breast cancer. However, more detailed studies are required to deepen understanding of liraglutide consequences in triple negative breast cancer. ▶Graphical Abstract.
Keywords: liraglutide; Triple negative breast cancer (TNBC); ATP- binding cassette (ABC) transporters; Glucagon-like petide-1 (GLP-1)